Trends in Children’s Dietary Inflammatory Index and association with prediabetes in U.S. adolescents - Zisu Chen; Jing Wu; Kepeng Ai; Zhuying Bu; Wenquan Niu; Min Li (Nutrition & Diabetes)
Abstract Background and Objectives Prediabetes is a high-risk state for diabetes. We aimed to illustrate secular trends in the Children’s Dietary Inflammation Index (C-DII) among U.S. adolescents and assess its association with prediabetes. Methods Adolescents aged 12–18 years were collected from the National Health and Nutrition Examination Survey, 2001–2018. Prediabetes was defined based on Hemoglobin A1c, fasting glucose, and glucose tolerance levels. Risk was quantified by odds ratio (OR) and 95% confidence interval (CI). Results A total of 13,684 adolescents were analyzed, representing a weighted total population of 33,351,181. C-DII scores declined significantly from 2001 to 2012 and increased from 2013 to 2018. The relationship between C-DII and prediabetes was roughly linear. When assigning the low C-DII scores as the reference, adolescents with medium and high C-DII scores were 1.22 (adjusted 95% CI: 1.04–1.44) and 1.25 (0.99–1.60) times more likely to have prediabetes. In subgroup analyses, the risk for prediabetes was significantly enhanced in boys (adjusted OR = 1.26 and 1.45 for medium and high C-DII scores, 95% CI: 1.05–1.51 and 1.09–1.92), and in adolescents living in poor families for medium (1.34 and 1.44, 1.08–1.67 and 1.07–1.95). Conclusions Our findings indicate a V-shaped secular trend in C-DII scores from 2001 to 2018 in U.S. adolescents, with the nadir in 2011–2012, and the risk for prediabetes was significantly increased by over 20% in adolescents possessing medium or high C-DII scores.